Fostering Reading Comprehension: Exploring EFL-Students’ Perception Using Quizizz and Its Relation to Their Proficiency - Irwan Sulistyanto; Krisna Adi Prayoga (Tell : Teaching of English Language and Literature Journal, 2025)
This study explores EFL students' perceptions of using Quizizz as an assessment tool in Basic Reading class and examines its correlation with their reading proficiency. A survey was conducted among 25 students using a closed-ended questionnaire, and their reading proficiency was assessed using final test scores. The findings reveal that students generally have a positive perception of Quizizz, particularly in terms of its interactive features, motivation enhancement, and immediate feedback. Correlation analysis indicates a significant relationship between students' perceptions and their reading proficiency, suggesting that higher engagement with Quizizz is associated with better reading outcomes. However, some technical difficulties and accessibility challenges were noted, emphasizing the need for additional training and support. The study concludes that integrating Quizizz in reading instruction enhances student engagement and proficiency, though further research is needed to explore long-term effects and broader implementation strategies.